Respuesta :
Answer:
2
Step-by-step explanation:
x is 3
y is 1
hence substitute: (3x3)divide by 3 - 1
is equal to 2
[tex]\huge\text{Hey there!}[/tex]
[tex]\mathsf{x^3 \div 3 - y}\\\\\mathsf{= \dfrac{x^3}{3} - y}\\\\\mathsf{= \dfrac{3^3}{3} - 1}\\\\\mathsf{= \dfrac{3\times3\times3}{3} - 1}\\\\\mathsf{= \dfrac{9\times3}{3} - 1}\\\\\mathsf{= \dfrac{27}{3} - 1}\\\\\mathsf{= 9 - 1}\\\\\mathsf{= 8}[/tex]
[tex]\huge\text{Therefore, your answer should be:}[/tex]
[tex]\huge\boxed{\frak{8}}\huge\checkmark[/tex]
[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]
~[tex]\frak{Amphitrite1040:)}[/tex]